Impact of Success Expectations, Motivation and Team Behavior on Entrepreneurship Learning Outcomes in Higher Education - Rahmat Eka Putra; Harif Amali Rivai; Hendra Lukito; Rebi Fara Handika (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
While there is ample evidence to support the direct impact of success expectations on academic achievement, little research has explored the motivational mechanisms that mediate success expectations–learning outcomes in the entrepreneurial context and student learning environment, and such studies are needed to understand how and why success expectations affect learning outcomes. For this purpose, it integrates the social cognitive approach of the theory of planned behavior (TPB) and the organismic theory of motivation of self-determination theory (SDT). More specifically, it tests the role of success expectations, motivation, and learning outcomes in the form of business ideas in an indirect conditional process where team behavior becomes a contextual variable. The sample consist of 231 students at several universities in Indonesia. Data is analyzed using structural equation modeling (SEM). The results show that students' motivation acted as a mediator between success expectations and learning outcomes, and team behavior strengthens the relationship. These results provide empirical evidence to better understand the mechanism of the success expectation–learning outcome. The implications of these findings are then discussed for teaching and learning in universities.